2003
DOI: 10.1002/dvdy.10359
|View full text |Cite
|
Sign up to set email alerts
|

Expression of NG2 proteoglycan during endochondral and intramembranous ossification

Abstract: We have used immunohistochemistry to study the distribution of the NG2 proteoglycan during bone development in the mouse. At embryonic day 15.5, NG2 was strongly detected in the immature cartilage of developing limbs. After transient down-regulation in mature chondrocytes, NG2 was up-regulated during primary ossification, colocalizing with alkaline phosphatase and tenascin C. In the epiphyseal growth plates of newborn mouse tibia, NG2 and alkaline phosphatase exhibited overlapping patterns of expression by hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 29 publications
1
37
0
1
Order By: Relevance
“…In the developing rodent limb, NG2 expression is not seen on undifferentiated stem cells of the early limb bud, but is upregulated in condensations of mesenchymal cells that represent immature chondroblasts. 26,27 As chondroblasts differentiate into mature chondrocytes, NG2 expression is largely downregulated. A similar pattern of up and downregulation is observed during the osteoblast to osteocyte transition in maturing bone.…”
Section: Ng2 Expression Outside the Central Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In the developing rodent limb, NG2 expression is not seen on undifferentiated stem cells of the early limb bud, but is upregulated in condensations of mesenchymal cells that represent immature chondroblasts. 26,27 As chondroblasts differentiate into mature chondrocytes, NG2 expression is largely downregulated. A similar pattern of up and downregulation is observed during the osteoblast to osteocyte transition in maturing bone.…”
Section: Ng2 Expression Outside the Central Nervous Systemmentioning
confidence: 99%
“…A similar pattern of up and downregulation is observed during the osteoblast to osteocyte transition in maturing bone. 27 In developing skin, NG2 is expressed by proliferating keratinocyte progenitor cells that are derived from slowly cycling, NG2-negative keratinocyte stem cells. [28][29][30] NG2 expression is also prominent on progenitor cells associated with the hair follicle bulge region.…”
Section: Ng2 Expression Outside the Central Nervous Systemmentioning
confidence: 99%
“…We also stained for the NG2 chondroitin sulfate proteoglycan (mouse anti-rat NG2, Chemicon, Temecula, CA), which is expressed by immature progenitor cells in several different lineages, including immature chondroblasts in limb development, vascular pericytes, and during both endochondral and intramembranous ossification. NG2 is felt to be one of the best available markers for pericytes in developing microvessels [6,20]. Double immunostaining for PCNA (brown signal in nucleus) and ED1 (blue signal in cell membrane) was performed using peroxidase staining with DAB and Vector SG (Vector Laboratories; Burlingame, CA), respectively.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…To confirm that FGFR1 ϩ cells were indeed pericytes, we analyzed their expression of the pericyte marker NG2 ( Figure 2F-G), and observed that FGFR1/2 ϩ cells in the avascular perichondrium did not express NG2, which was instead expressed by chondrogenic progenitors, as described previously. 28 Conversely, some periosteal FGFR1 ϩ cells did coexpress NG2, but the expression patterns of those 2 markers were not completely overlapping. Similarly, CD146, another marker of pericytic MSCs, did not show extensive colocalization with NG2 ( Figure 2H).…”
mentioning
confidence: 98%